David Malcolm - Lloyd, Nelson, 1873-1933 (Salt Lake City, UT : Project Gutenberg, 2007)
"David Malcolm" by Nelson Lloyd is a novel written in the early 20th century. It centers on a young boy named David Malcolm, who embarks on an adventure to go fishing in the mountains, encountering various characters along the way that reflect the worries, fears, and quirks of his small-town life. The narrative begins with David's innocent defiance against his mother$1 (Bs warnings and soon introduces a mysterious and complex figure, the Professor, who hints at deeper societal issues. The opening of the novel presents David as a confident, adventurous child excited about his fishing trip. As he sets off under the watchful gaze of his mother, her concerns about danger$1 (Bsuch as falling into the water or encountering rattlesnakes$1 (Bare depicted humorously, setting the tone for David$1 (Bs youthful bravado. He interacts with various townsfolk, including the Reverend Mr. Pound and Squire Crumple, who voice exaggerated warnings that add an element of foreshadowing. The story takes a darker turn when David meets Penelope Blight and her father, who is soon revealed to have a troubled reputation in the village as "the Professor." This pivotal encounter sets the stage for future conflicts involving societal judgment and the price of nonconformity, foreshadowing an exploration of themes like adventure, innocence, and the struggle for identity against societal expectations. (This is an automatically generated summary.)s
Release date is 2007-12-05
Produced by Al Haines
Keywords: Fiction